Values Matter, Don't They? – Combining Theory of Planned Behavior and Personal Values as Predictors of Social Entrepreneurial Intention. Issue 1 (2nd January 2019) - Kruse, Philipp; Wach, Dominika; Costa, Sílvia; Moriano, Juan Antonio
Abstract: In the face of growing social inequality, social entrepreneurship (SE) is considered to be a sustainable way to account for unmet social needs. Research acknowledges that SE-intention is an important prerequisite for SE-activity but there is only limited knowledge about the mechanisms of SE-intention formation. Despite theories with a cognitive focus like the Theory of Planned Behavior (TPB) having been shown to be able to predict SE-intention, the influence of an individual's goal orientations, i.e. one`s personal values, on the choice to pursue a career as a social entrepreneur has been largely neglected. By integrating the TPB and Basic Human Values Theory, we investigate the mechanisms through which personal values are related to SE-intentions. Structural-Equation-Analyses with a sample of German university students ( N = 1, 326) yielded positive direct effects for the personal value dimensions of openness and self-transcendence, and negative direct effects for conservation and self-enhancement on SE-intention. Furthermore, indirect effects of self-transcendence and self-enhancement via the TPB-components emerged. Further research is needed to consolidate our findings and examine potential intercultural differences of value influences on SE-intention formation. The practical implications are that the educators of potential social entrepreneurs should invest more effort in securing a fit of personal values and the values that reinforce SE. Furthermore, our results highlight that making women aware of the possibility of combining social and financial value goals in SE could increase the number of female entrepreneurs.